2019
DOI: 10.1016/j.jpcs.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene fluoride/magnetite nanocomposites: Dielectric and thermal response

Abstract: Nanocomposites of poly (vinylidene fluoride), PVDF, and magnetite (Fe 3 O 4 ) nanoparticles were prepared using the twin screw compounding method and the effect of filler concentration (5-15 wt%) on the thermal stability, dielectric properties and dielectric strength were investigated. It was observed that the dynamic characteristics of crystalline α c -relaxation peak remain almost constant for the composites studied; while the activation energy plots almost coincide indicating that the time scale of this rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Blends of poly(vinylidene fluoride) (PVDF) and magnetic particles, to induce advantageous properties in addition to PVDF's piezoelectricity, are gaining attention [1][2][3][4][5] and are being studied for stimulation of cells. [6] Different processing techniques for electroactive polymers have been studied; [7] however, many require volatile solvents or lack control over the design and/or the resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Blends of poly(vinylidene fluoride) (PVDF) and magnetic particles, to induce advantageous properties in addition to PVDF's piezoelectricity, are gaining attention [1][2][3][4][5] and are being studied for stimulation of cells. [6] Different processing techniques for electroactive polymers have been studied; [7] however, many require volatile solvents or lack control over the design and/or the resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO nanofiller also increased the temperature of crystallization ( Figure S2 ), reaching up to ≈7 °C higher for both cooling rates. Samples with 10–15% ZnO also depict a narrower crystalization peak compared to pristine PVDF, suggesting a narrow crystallite size distribution [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several works showed that magnetite is a promising material for high dielectric constant nanocomposites 53,54 , which is another key advantage to achieve high electromagnetic absorption.…”
Section: Magnetisation and Electromagnetic Shielding Efficiencymentioning
confidence: 99%